Note sul confronto fra Lutto e melanconia di Freud e Una depressione di Fagioli - De Simone, Gianfranco (Il sogno della farfalla, 2023)
The aim of this paper is to propose a comparison between Mourning and melancholia by Freud and A depression by Fagioli, which are the only works written by these authors on depression. These writings allow to identify at the same time both their theoretical and methodological frameworks and their radical differences. More specifically, the authors drastically differ in their way of conceiving the non-conscious dimensions of depression, the consequent psychotherapeutic rapport, and more generally the non-conscious mind and its alterations. According to Freud, melancholia is a narcissistic disorder which manifests in a subject who did not manage during childhood to transition from love for a narcissistic object to an objectual love for another individual. On the contrary, Fagioli sets at the core of the therapeutic rapport for the cure of depression the importance to face dimensions such as grief for the loss of affection, the impossibility of knowing, the connection between oneiric images’ alteration and the suffering of the body.